2012
DOI: 10.1371/journal.pone.0036936
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Determinants of Metabolic Syndrome among Women in Chinese Rural Areas

Abstract: Background and AimsMetabolic syndrome (MS) is prevalent in recent years but few data is reported in the rural areas in China. The aim of this study was to examine MS prevalence and its risk factors among women in rural China.Methods and ResultsThe Nantong Metabolic Syndrome Study (NMSS), a population based cross-sectional study, was conducted during 2007–2008 in Nantong, China. In person interviews, blood glucose and lipid measurements were completed for 13,505 female participants aged 18–74 years. The Interna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
48
1
4

Year Published

2013
2013
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 54 publications
6
48
1
4
Order By: Relevance
“…Furthermore, as observed in other studies, the low education level of our study group had a negative effect on the prevalence of MetS. (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 73%
“…Furthermore, as observed in other studies, the low education level of our study group had a negative effect on the prevalence of MetS. (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29).…”
Section: Discussionsupporting
confidence: 73%
“…However, earlier studies of MetS have shown a J-shaped relationship between alcohol intake and the risk of MetS [31][32][33]. Indeed, light alcohol consumption was actually associated with a lower risk of MetS [32][33][34], while very heavy alcohol consumption was associated with a substantial increase in the risk of MetS [35]. The differences in the relationship between alcohol intake and the risk of clustering of MetRFs might be related to differences in obesity status of the subjects, namely, non-obese versus obese.…”
Section: Discussionmentioning
confidence: 99%
“…The effects of physical activity and energy intake on MetS have been examined in numerous studies [8][9][10][11][29][30][31][32]. However, few studies have examined their effects in non-obese subjects with a clustering of MetRFs.…”
Section: Discussionmentioning
confidence: 99%
“…Insulin-resistance is known to be associated with a more severe PCOS phenotype. Moreover, insulin sensitivity is known to be related to many environmental factors, such as physical activity, diet, and alcohol consumption, among others [11]. The failed could not find any studies focusing on the problem of the different prevalence of insulin-resistance in urban and rural areas; however, there are few analyzing the occurrence of metabolic syndrome.…”
Section: Discussionmentioning
confidence: 99%